Improved LDPC-based short-range frequency-hopping wireless communication system - Wei-dong FANG; Wu-xiong ZHANG; Ming-ming HU; Wei CHEN; Yang YANG (Tongxin xuebao)
In short-range wireless communication system(SWCS)，the complex scenarios make its transmission face the diverse interference，and lower hardware resource leads to its limited anti-interference capability.To achieve the reliable transmission，a frequency-hopping-based SWCS (FH-SWCS)with improved LDPC (I-LDPC) code was constructed.In FH-SWCS，a low-complexity check-sum updating(LCU)algorithm was proposed to reduce the amount of computation.LCU-based multi-threshold bit flipping (LCU-MTBF) algorithm was given to increase the reliability of bit-flipping， improving decoding performance and reduce the complexity of decoding.The simulation results demonstrate that LCU is suitable for multiple hard decisions decoding algorithm，and it can reduce the computational complexity of original decoding algorithm without affecting its performance.When BER is 10−5，and iterations number is 5，0.15dB performance gain can be achieved，and the number of additions algorithm can be reduced about 40% in LCU-MTBF.In FH-SWCS with I-LDPC，when BER is 10−4，and SNR is 15dB，the performance gain about 7dB can be achieved to improve the anti-interference of the system effectively.